Layanan Konseling Kelompok Dengan Teknik Diskusi Kelompok Untuk Meningkatkan Kepercayaan Diri - Hilma Sadatil Alawiyah; Ageng Saepudin Kanda. S (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state.improving the quality in the implementation of education by improving the curriculum, facilities and infrastructure that support education and improving the learning process, one of which is by improving learning methods.There are various kinds of learning methods themselves, namely the discussion method. The discussion method is a process of activities carried out consciously by students to achieve goals carried out in groups or from the results of learning activities in groups with fellow students.The group discussion method has several benefits when implemented in educational institutions, one of which is increasing children's self-confidence, with the aim of growing and developing children's self-confidence, especially children's self-confidence in socializing. So that children can unleash their potential to the maximum and have the possibility to do better if supported by adequate training and facilities through the discussion method.